Hypothermia in acutely presenting burn injuries to a regional burn service: The incidence and impact on outcome - M.R. Lukusa; N.L. Allorto; S.L. Wall (Elsevier, 2021)
Background: Hypothermia in burns has been associated with increased mortality when adjusting for burn severity. This study looks at the incidence of hypothermia among burn patients presenting acutely to the Pietermaritzburg Burn Service and its impact on patient outcome specifically sepsis and mortality. Methodology: A retrospective review was conducted using the existing burns database. All acute burns admissions to the PBS between 1 February 2016 and 31January 2018 were considered. Variables analyzed include: Age, Gender, time from burn to admission, mechanism of burn, total body surface area (TBSA), inhalation burn and intubation, admission temperature, time to first septic episode, length of stay and final outcome. Hypothermia was defined as body temperature less than 36 degrees Celsius. Results: Three-hundred-and-one patients were included in the study. Thirty-four percent were hypothermic. In the paediatric patients, age and TBSA were significant predictors of hypothermia. There was an association between hypothermia and the incidence of sepsis and time to first episode of sepsis in this group. In the adult population, TBSA and the presence of inhalation injury both had a significant impact on hypothermia. In this group, there was an association between hypothermia and length of hospital stay as well as mortality. Conclusion: Hypothermia in acutely presenting burn injuries has a significant impact on outcome. In paediatric patients this is an increase in early sepsis and in adults patients an increase in length of hospital stay and mortality. Efforts need to be made, right from the pre-hospital setting, to ensure patient warming to prevent hypothermia.